Antibacterial Effectiveness Test on the Combination of Kersen Leaf (Muntingia calabura L.) and Jackfruit Leaf (Artocarpus heterophyllus L.) Extracts Against The Growth of Staphylococcus aureus Bacteria - Mahendri, Adelia Citra; Suswidiantoro, Vicko; Pratiwi, Mida; Pisacha , Iga Mayola (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Kersen leaves (Muntingia calabura L.) and jackfruit leaves (Artocarpus heterophyllus L.) are tropical plants that grow in Indonesia. The phytochemical content of kersen leaves and jackfruit leaves include flavonoids, tannins and saponins. Flavonoids have antibacterial properties because they can fight bacteria in several ways. These substances can interfere with the formation of bacterial genetic material (nucleic acids), damage cell membranes that maintain the contents of bacterial cells, and inhibit the processes used by bacteria to produce energy. This study aims to determine the effectiveness of secondary metabolite compounds against the growth of Staphylococcus aureus bacteria contained in kersen leaves and jackfruit leaves. The research method used is experimental. The sample in this study was a combination of 96% ethanol extract of kersen leaves (Muntingia calabura L.) and jackfruit leaves (Artocarpus heterophyllus. L). The yield of extracts obtained in kersen leaves amounted to 32.1% and avocado leaves 25.42%. Phytochemical screening showed that both samples contained secondary metabolites such as flavonoids, tannins and saponins. The combination of kersen leaf and jackfruit leaf extracts at a concentration ratio of 80:50% and has an average inhibition zone with high effectiveness of 11.10 mm which is classified as strong. This shows that there is a difference, the inhibition zone is better than ampicillin in inhibiting Staphylococcus aureus bacteria.